The relationship between trans-femoral prosthesis alignment and the center trajectory of plantar pressure in the frontal plane - Nomura, Tomohiro; Watanabe, Kota; Nosaka, Toshiya; Matsubara, Hiroyuki; Akiyama, Masaharu; Inui, Kimiharu (Journal of Physical Therapy Science, 2016)
[Purpose] It is difficult to identify by visual observation whether alignment abnormalities in trans-femoral prostheses in the frontal plane are attributable to the adduction angle or the abnormal alignment of the positions of the medial and lateral sides of the socket in relation to the foot. Therefore, we focused on the trajectory of the center of plantar pressure during walking, and we proposed a method for differentiating these two alignment abnormalities. [Subjects and Methods] We recruited 4 trans-femoral unilateral amputees. Bench alignment was achieved initially. We compared the amplitude of the trajectory of the center of plantar pressure when walking under 2 conditions: 1) when changing the adduction angle and 2) when changing the positional relationship between the socket and the foot. [Results] It was not possible to distinguish between the 2 types of malalignment on the prosthesis side. There was a significant difference when changing the positional relationship on the contralateral side. Thereby, the plantar pressure of the contralateral side could be used to distinguish between the 2 types of malalignment. [Conclusion] The results of this study suggested that trans-femoral prosthesis malalignment could be evaluated through the plantar pressure of the contralateral side in amputees.